A fuzzy AHP methodology for selection of risk assessment methods in occupational safety. (2015) - Guneri, Ali Fuat; Gul, Muhammet; Ozgurler, Senim
In modern times daily occupational accidents cause an ever increasing number of pecuniary loss claims as well as intangible damage within small and medium sized enterprises (SMEs) worldwide. To counter this problem, most enterprises commonly apply risk assessment methods (RAMs) to promote occupational safety (OS). As there are plenty of different methods in this area, an effective and careful approach is required to select the most appropriate RAM for enterprises in general. This paper provides a fuzzy analytic hierarchy process (AHP) methodology for selecting the best RAM in OS operations for SMEs. As a test case study, a Turkish woven-printed-carton labelling company was chosen to carry out this study application under four separate decision criteria namely: scope, practicality, cost and sensitivity. On conclusion, it was deduced that the decision making approach can benefit company management in selecting the right method for OS operations.